2022
DOI: 10.3389/fnana.2022.851432
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype and Distribution of Immature Neurons in the Human Cerebral Cortex Layer II

Abstract: This work provides evidence of the presence of immature neurons in the human brain, specifically in the layer II of the cerebral cortex. Using surgical samples from epileptic patients and post-mortem tissue, we have found cells with different levels of dendritic complexity (type I and type II cells) expressing DCX and PSA-NCAM and lacking expression of the mature neuronal marker NeuN. These immature cells belonged to the excitatory lineage, as demonstrated both by the expression of CUX1, CTIP2, and TBR1 transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…IPs express the canonical marker EOMES (Englund et al 2005). IP clusters share transcriptomic signatures with neurons (ROBO1 (Ip et al 2011), CUX1 (Coviello et al 2022)), as has been previously reported in organoid scRNA-seq studies (Quadrato et al 2017;Velasco et al 2019). Some neural progenitor cells (NPCs) expressed S phase markers or G2/M phase markers in addition to VIM and PAX6.…”
Section: Organoids Produce Expected Cell Typessupporting
confidence: 59%
“…IPs express the canonical marker EOMES (Englund et al 2005). IP clusters share transcriptomic signatures with neurons (ROBO1 (Ip et al 2011), CUX1 (Coviello et al 2022)), as has been previously reported in organoid scRNA-seq studies (Quadrato et al 2017;Velasco et al 2019). Some neural progenitor cells (NPCs) expressed S phase markers or G2/M phase markers in addition to VIM and PAX6.…”
Section: Organoids Produce Expected Cell Typessupporting
confidence: 59%
“…These neurons can re-activate their maturational process to finally mature and integrate into adult circuits ( Rotheneichner et al, 2018 ; Benedetti et al, 2020 ). This “neurogenesis without division” can be important for two reasons: first, because they can represent a reservoir of new elements in brain regions that are not endowed with stem/progenitor cells (e.g., the cerebral cortex; Rotheneichner et al, 2018 ; La Rosa et al, 2019 , 2020b ; Coviello et al, 2022 ); second, because it may explain why DCX + cells can be found in non-neurogenic regions, in the absence of cell division. The molecular mechanisms responsible for the stop/re-start of the maturational process, as well as the role they can play once inserted in the circuits, are currently unexplored ( Benedetti and Couillard-Després, 2022 ).…”
Section: Canonical and Non-canonical Neurogenesis: From Neural Stem C...mentioning
confidence: 99%
“…Strong evidence suggests that immature neurons in the amygdala are destined to become excitatory neurons (Sorrells et al, 2019), but it is still largely debated whether immature neurons in layer II of the cerebral cortex are destined to become principal excitatory neurons or inhibitory interneurons (Cai et al, 2009; König et al, 2016; Luzzati et al, 2009; Varea et al, 2011; Xiong et al, 2010; Zhang et al, 2009). Although some discrepancies between studies can be attributed to technical and inter‐species differences, most studies that have tried to decipher the identity and fate of immature neurons in layer II of the cerebral cortex did not necessarily focus on specific cortical regions (Coviello et al, 2022; Luzzati et al, 2009; Varea et al, 2011; Xiong et al, 2008), raising the possibility that region‐specific differences exist.…”
Section: Discussionmentioning
confidence: 99%